PENDIDIKAN KARAKTER DI MADRASAH IBTIDAIYAH - Hamdi Abdul Karim (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2016)
Character education in Indonesia focuses not only on the understanding of the students conceptual and contextual, but also expected of the students were able to create and innovate appropriately. The implementation of character education in Government Elementary School, is expected to be a solution to social problems that occur in the community. The implementation of character education in Madrasah Ibtidaiyah can be implemented in the areas of learning (learning activities), cultural development of the school, extracurricular activities, and daily activities at home.